Sarcoglycanopathies: state of the art and therapeutic perspectives - Fernández-Eulate, Gorka; Leturcq, France; Laforêt, Pascal; Richard, Isabelle; Stojkovic, Tanya (M.S. Médecine sciences, 2020)
Sarcoglycanopathies are the third most common cause of autosomal recessive limb girdle muscular dystrophies (LGMD). They are the result of a deficiency in one of the sarcoglycans a, b, g, or d. The usual clinical presentation is that of a symmetrical involvement of the muscles of the pelvic and scapular girdles as well as of the trunk, associated with more or less severe cardio-respiratory impairment and a marked increase of serum CK levels. The first symptoms appear during the first decade, the loss of ambulation occurring often during the second decade. Lesions observed on the muscle biopsy are dystrophic. This is associated with a decrease or an absence of immunostaining of the sarcoglycan corresponding to the mutated gene and, to a lesser degree, of the other three sarcoglycans. Many mutations have been reported in the four incriminated genes and some of them are prevalent in certain populations. To date, there is no curative treatment, which does not prevent the development of many clinical trials, especially in gene therapy.